Regulatory RNAs Basics, Methods and Applications - Mallick, Bibekanand; Ghosh, Zhumur (Springer Berlin Heidelberg : Imprint: Springer, 2012)
Recent progress in high-throughput technologies and genome wide transcriptome studies have lead to a significant scientific milestone of discovering non-coding RNAs (ncRNAs) which spans through a major portion of the genome. These RNAs most often act as riboregulators, and actively participate in the regulation of important cellular functions at the transcriptional and/or post-transcriptional levels rather than simply being an intermediated messenger between DNA and proteins. As the appreciation for the importance of ncRNAs continues to emerge, it is also increasingly clear that these play critical roles in gene regulatory processes during development and differentiation. Further, regulatory RNAs are useful biomarkers for diagnosis of diseases. Hence these RNA regulators are essential to the development of therapeutics. This book on "Regulatory RNAs" offers a comprehensive view on our current understanding of these regulatory RNAs viz. siRNA, miRNA, piRNA, snoRNA, long non-coding RNA, small RNA etc. It addresses both the biogenesis and mechanism of action of regulatory RNAs with a primary focus on their annotation, experimental methodologies (microarray, next-gen sequencing etc.) for their discovery, computational tools for their prediction, and above all, applications of these revolutionary regulatory molecules in understanding biological systems and diseases, including therapeutics. This comprehensive volume is intended for readers with research or teaching interests in ncRNA biology and will provide a major information resource on current research in the fast-moving fields of RNA and gene expression regulation. Cutting-edge and concise, "Regulatory RNAs: Basics, Methods and Applications" promises to support vital research in the field of regulatory RNAs, ever-continuing to grow rapidly and gain increasing importance in basic and translational biology.